Development characteristics and main controlling factors of Carboniferous volcanic reservoirs in the Shixi area, Junggar Basin - Yiming, Abulimiti; Bian, Baoli; Liu, Hailei; Wang, Jiangtao; Wang, Xueyong; Zhu, Junyong; Zhu, Yongcai; Liu, Longsong; Su, Dongxu (Frontiers in Earth Science, 2023)
The Carboniferous volcanic reservoirs in the Shixi area of the Junggar Basin are complex and diverse. Identifying the characteristics and main factors controlling high-quality volcanic reservoirs is the key to increasing oil and gas reserves and production in this area. Through core observations, thin section identification, physical property and pore structure analyses, combined with production data, the main controlling factors and development modes of high-quality reservoirs were analysed. The results show that the Carboniferous strata in the Shixi area mainly contain andesite and dacite of overflow facies, followed by volcanic breccia and tuff of explosive facies. Volcanic reservoirs in the study area are high-porosity–low-permeability and medium-porosity–low-permeability reservoirs. Volcanic breccia of explosive facies has the best physical properties, showing the characteristics of high porosity and medium permeability. The reservoir space is mainly composed of gas cavities, corrosion pores and fractures, among which the corrosion pores are the most important reservoir spaces of the Carboniferous volcanic rocks. Lithology and lithofacies, weathering and corrosion, and fractures are the main factors controlling the development of high-quality volcanic reservoirs. Volcanic rocks that had experienced weathering and denudation for a long time developed a large number of secondary corrosion pores due to the corrosion of soluble minerals or volcanic ash. Fractures further improved the physical properties, causing volcanic rocks to eventually develop into weathering crust reservoirs. The physical properties of the volcanic rocks far away from the weathering crust were improved through primary gas cavities and structural fractures, and these volcanic rocks eventually developed into the inner reservoir.